RESEARCH OF ECOLOGO-ENERGY AND ECONOMIC EFFICIENCY OF USING SMART-TECHNOLOGIES IN THE SYSTEM OF THERMAL CONSUMPTION OF BUILDINGS: Array - , А. П., Ю. Л., М. Ф., В. Є., С. В. (Municipal economy of cities. Series: «Economy science», 2018)
A comprehensive analysis of the energy, environmental and economic efficiency of use in the systems of heat consumption of buildings of SMART-technologies for managing thermal conditions of heated premises was carried out. А natural object was selected and investigated for the introduction of energy-saving technologies - a 3-storey fragment of the administrative building of O.M. Beketov National University of Urban Economy in Kharkiv with a total area of heated premises of 225.3 m2; investigated: structure, basic elements, principle of operation, efficiency of application of an automated system for controlling thermal conditions of rooms. The effectiveness of the application of such a system was evaluated according to the following criteria: relative and absolute values of reducing thermal energy for heating a building - a natural object, reducing carbon dioxide emissions - CO2 as the main greenhouse gas, and the economic effect of saving thermal energy. The method of evaluating the efficiency of heat management on the natural object is broken down. The calculation of heat losses was carried out at round-the-clock temperature in rooms of +18 ° C for monthly average outdoor air temperatures in the city of Kharkiv during the heating seasons of 1981–2016. Analysis of the results of calculations shows that the use of a remote control system for thermal conditions of the premises allows to achieve savings of 4709 kW • h of thermal energy during the heating season and reduce the cost of heating the building - a natural object by 16.6%. As a result of reducing the consumption of thermal energy, the reduction of greenhouse gas (CO2) emissions resulting from fuel combustion is 0.95 tons/year; The economic effect of reducing the cost of using thermal energy ha heating season is 6430 UAH. Keywords: heat consumption, rational nature management, heating system, natural object, smart-technology, energy efficiency, environmental friendliness, economic effect.